2009
DOI: 10.2109/jcersj2.117.439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of raw powder size, reaction temperature, and soaking time on synthesis of SiC/SiO2 coaxial nanowires via thermal evaporation

Abstract: High-yield SiC/SiO2 core-shell nanowires were synthesized without adding metal catalysts from outside through a simple thermal evaporation of silicon powders during decomposition of methane gas. The influence of three parameters, size of Si raw powder (50 nm and 5 μ m), reaction temperature (1573, 1623 and 1673 K), and soaking time (1, 3 and 6 h), was investigated.The typical synthesized nanowires from different conditions possess the diameter of no thicker than 100 nm with several tens micrometers in length. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…3, and five diffraction peaks could be identified as (1 1 1), (2 0 0), (2 2 0), (3 1 1) and (2 2 2) reflections of ␤-SiC without any other impurities. From the transmission electron microscope (TEM) observation, and Fourier-transform infrared spectroscopy (FT-IR) characterizations in our previous work [22], it was confirmed that the SiCNWs produced by this process were core-shell type nanowires those had a single crystal ␤-SiC core and low-crystalline SiO 2 shell.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…3, and five diffraction peaks could be identified as (1 1 1), (2 0 0), (2 2 0), (3 1 1) and (2 2 2) reflections of ␤-SiC without any other impurities. From the transmission electron microscope (TEM) observation, and Fourier-transform infrared spectroscopy (FT-IR) characterizations in our previous work [22], it was confirmed that the SiCNWs produced by this process were core-shell type nanowires those had a single crystal ␤-SiC core and low-crystalline SiO 2 shell.…”
Section: Resultsmentioning
confidence: 62%
“…Silicon powder (average particle size 5 m, 99.99% purity, Kojundo Chemical Laboratory Co., Ltd., Japan) was pre-oxidized in air at 800 • C for 1 h to increase the oxygen content in the raw powder as mentioned in the previous research [22]. Oxidized silicon powder was placed in a mullite boat which was covered with an alumina fiber net (3025-T Standard Woven Fabric, Nitivy Co., Ltd., Japan), and was carefully put in the center of a mullite tube furnace as schematically shown in Fig.…”
Section: Synthesis and Characterization Of Sicnwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a CVD method can be employed making use of Fe as catalyst and methane as precursor (Zang et al, 2002). A high yield core/shell SiC/SiO 2 NW production method without the use of catalyst was developed starting from raw powders of Si via an oxide assisted thermal evaporation process (Khongwong et al, 2009). Core-shell SiC NW have also been synthesized from carbon monoxide using Ni catalyst by carbothermal reduction method (Attolini et al, 2008).…”
Section: A Brief Review Of Nw Growth Methodsmentioning
confidence: 99%
“…Four fundamental growth mechanisms were proposed to explain the growth model of nanowires, including VS, VLS, solid-liquid-solid (SLS) and oxide assisted growth (OAG), in which VS and VLS mechanisms were most commonly involved [33][34][35]. On the basis of experimental results, a catalyst-free VS growth mechanism was proposed to disclose the growth model of several millimeters long SiC-SiO 2 nanowires.…”
Section: Growth Mechanism Of Several Millimeters Long Nanowiresmentioning
confidence: 99%